Pengaruh Kampanye Public Relations #Generasikulit Sehat Terhadap Brand Image Npure (Survei Terhadap Followers Instagram @Npureofficial) - Dinda Putri Yulianti; Nani Nurani Muksin (STIKes Ibnu Sina Ajibarang, 2024)
The rise of the new cosmetics industry with various levels of companies has an impact on the number of cosmetics lovers and users in Indonesia. In this case, the company must form and improve its brand image to differentiate the company from its competitors. As a local beauty brand, Npure is campaigning #SehatSkinGeneration which is uploaded via Instagram with the hope that there will be new generations who will speak up and care about the process towards healthy skin for both men and women and of all age groups. This research was conducted to measure how much influence the #SehatSkinGeneration campaign has on the Npure Brand Image. The theories used in this research are Public Relations Campaign theory (Newsom, Scoot, & Turk (1997:475) (in Ruslan, 2021:96) and Brand Image theory (Kotler Keller, 2013). The approach in this research uses quantitative methods. survey by distributing questionnaires to 78 samples that have been determined using the Solvin formula calculation with sampling using random sampling The influence of the public relations campaign on brand image is 64.6%, this figure means that the influence of the two variables is high, while the remaining 35.6% is influenced by other factors outside the research variables. By proving the existence of an influence, the results of the hypothesis test are 20.005 > 1.665, then Ho is rejected and H1 is accepted, which means the regression coefficient is significant, namely that there is an influence between the Public Relations Campaign and Brand Image Npure.